A study of efficacy of phage amplification technique in diagnosis of pulmonary and extra-pulmonary tuberculosis - Singh, Jai Pratap (International Journal of Advances in Medicine, 2019)
Background: Tuberculosis (TB) is a leading infectious disease in India. Diagnosis of TB has always been a problem due to slow rate of growth of Mycobacterium tuberculosis. In this study, author had compared the conventional tools for diagnosis of TB with the new Fast Plaque TBTM. Methods: The study was conducted at Dr. ML Chest Hospital, Department of Tuberculosis and Respiratory Diseases, G.S.V.M. Medical College, Kanpur. Specimens were collected after taking informed consent from patients attending outpatient and indoor patients admitted in the hospital. Study consisted of cases having suspected tuberculous exudation both pulmonary and extra pulmonary. Results: Most of the patients in this study were between 21-40years of age. Most of them were male (78%). Most of the patients came from urban areas and middle socioeconomic strata. Among them 68% were smokers and 32% were non-smokers. Comparison of phage assay with clinical evidence of disease has been done and results were sensitivity 85.7%, specificity 100%, PPV 100%, NPV 84.6% found. Conclusions: Delay in diagnosis resulting in further delay to initiate drug therapy. In these circumstances the rapid detection of mycobacteria by phage amplification technique could lead to earlier institution of antitubercular treatment.